2009
DOI: 10.1111/j.1365-2133.2008.08941.x
|View full text |Cite
|
Sign up to set email alerts
|

Itch characteristics in atopic dermatitis: results of a web-based questionnaire

Abstract: The questionnaire was found to be a useful tool in characterization of itch. Pain appears to be an important component of atopic dermatitis. The strong correlation between itch descriptors and itch intensity suggests that such descriptors serve as strong indicators of the symptomatology in atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 6 publications
1
118
1
12
Order By: Relevance
“…Dies wird jedoch oft nicht der Dynamik, den tageszeitlichen Schwankungen und der Schwere des Symptoms sowie der psychosozialen Belastung gerecht. In den letzten Jahren wurden Fragebögen zur Erfassung und Dokumentation von Pruritus bei bestimmten Erkrankungen entwickelt und eingesetzt [6,8,9,27,30,31,32]. In deutscher Sprache steht seit 1997/2001 der Eppendorfer Juckreizfragebogen zur Verfügung [6,8].…”
Section: Hintergrund Und Erste Ergebnisseunclassified
“…Dies wird jedoch oft nicht der Dynamik, den tageszeitlichen Schwankungen und der Schwere des Symptoms sowie der psychosozialen Belastung gerecht. In den letzten Jahren wurden Fragebögen zur Erfassung und Dokumentation von Pruritus bei bestimmten Erkrankungen entwickelt und eingesetzt [6,8,9,27,30,31,32]. In deutscher Sprache steht seit 1997/2001 der Eppendorfer Juckreizfragebogen zur Verfügung [6,8].…”
Section: Hintergrund Und Erste Ergebnisseunclassified
“…This hedonic experience is associated with activation of the reward system including the midbrain, striatum, anterior cingulate cortex (ACC) and orbitofrontal cortex (OFC) (Papoiu et al, 2013;Mochizuki et al, 2014). Studies using questionnaires have demonstrated that chronic itch patients rate scratching as pleasurable and that correlated well with their itch intensity (Dawn et al, 2009;O'Neil et al, 2011). It was also reported that in chronic itch patients, despite being initially somewhat pleasurable, scratching could lead to a counterproductive effect: an increase in the intensity of itch, which contrasts with the effect of scratching in healthy volunteers (Ishiuji et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Heat may play a harmful role in some AD patients by provoking perspiration, which is one of the most commonly reported aggravants in children with AD [139][140][141][142][143]. Perspiration may have an irritant effect on the skin mediated by the acidic pH of sweat, possibly promoting Th-2 inflammation [88], increased cutaneous blood flow due to vasodilation in hot environments [142], and possibly a neuroanatomic mechanism mediated by C nerve fibers [144].…”
Section: Climatementioning
confidence: 99%